2005
DOI: 10.1126/science.1106478
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of hsp70i Gene Bookmarking

Abstract: In contrast to most genomic DNA in mitotic cells, the promoter regions of some genes, such as the stress-inducible hsp70i gene that codes for a heat shock protein, remain uncompacted, a phenomenon called bookmarking. Here we show that hsp70i bookmarking is mediated by a transcription factor called HSF2, which binds this promoter in mitotic cells, recruits protein phosphatase 2A, and interacts with the CAP-G subunit of the condensin enzyme to promote efficient dephosphorylation and inactivation of condensin com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
181
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 159 publications
(196 citation statements)
references
References 20 publications
9
181
1
5
Order By: Relevance
“…HSF2 has previously been shown to bind to the hsp70i promoter during mitosis to mediate bookmarking of the hsp70i gene promoter [12]. Since our results showed that HSF2 and PRC1 interact during mitosis, we hypothesized that PRC1 could also be present at the hsp70i promoter.…”
Section: Prc1 Associates With the Hsp70i Promoter During Mitosismentioning
confidence: 63%
See 4 more Smart Citations
“…HSF2 has previously been shown to bind to the hsp70i promoter during mitosis to mediate bookmarking of the hsp70i gene promoter [12]. Since our results showed that HSF2 and PRC1 interact during mitosis, we hypothesized that PRC1 could also be present at the hsp70i promoter.…”
Section: Prc1 Associates With the Hsp70i Promoter During Mitosismentioning
confidence: 63%
“…In this epigenetic mechanism, HSF2 bound to the hsp70i promoter recruits PP2A and inactivates the CAP-G subunit of condensin resulting in a region of DNA that remains "open" and allows for a rapid transition to a transcriptionally active state in early G1 of the cell cycle [12]. With the characterization of this phenomenon involving HSF2, the question remained as to whether other functions and interactions involving HSF2 in mitosis have yet to be discovered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations